CCNP security secure 642-637 official cert guide - Wilkins, Sean; Smith, Franklin H. (Indianapolis, IN : Cisco Press, 2011)
Focuses specifically on the objectives for the CCNP Security SECURE exam. Share preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills.
Includes bibliographical references and index.
oif 24/06/15
Loans
Keywords: Computer networks; Telecommunications engineers